Characterization of a loess-paleosols section including a new record of the last interglacial stage in Pampean plain, Argentina - Tofalo, Ofelia Rita de Las Mercedes (2011)
A new record of the Marine Isotopic Stage 5, the last Interglacial Stage before present is presented in this paper. Sedimentological, micromorphological, trace elements analyses (Rb-Sr) and magnetic polarity determination were performed on Buenos Aires and Ensenada Formation (Late Cenozoic) deposits in the southern Chaco-Pampean Basin (Argentina). This work aims to unravel paleoclimatic and paleoenvironmental information from the analyzed data. The studied deposits encompass a complex and cyclic 8 m-thick sedimentary-pedogenetic sequence formed by loessic sediments and paleosols with volcano-pyroclastic provenance. Four tabular units, with net base and top, were defined from erosion surfaces. An OSL age >126 kyr was obtained from the upper middle part of unit B, which suggests that this unit as well as unit C, could have developed during the latest interglacial stage, equivalent to MIS 5. The occurrence of calcretes indicates periods of little clastic supply and seasonal arid or semiarid climate while iron oxides, smectites and illite-bearing pedogenetic calcretes point to annual rain rates between 100 and 500 mm. No calcretes of any origin occur in present soils of the same zone. According to our proposed interpretation of the available data, climate during MIS 5 was drier than today. The drier conditions may have been related to lower temperatures during summer.